Plasticity of the muscle proteome to exercise at altitude - Flueck, M. (High Altitude Medicine & Biology, 2009)
The ascent of humans to the summits of the highest peaks on Earth initiated a spurt of explorations into the physiological consequences of physical activity at altitude. The past three decades have demonstrated that the resetting of respiratory and cardiovascular control with chronic exposure to altitudes above 4000m is accompanied by important structural-functional adjustments of skeletal muscle. The fully altitude-adapted phenotype preserves energy charge at reduced aerobic capacity through the promotion of anaerobic substrate flux and tighter metabolic control, often at the expense of muscle mass. In seeming contrast, intense physical activity at moderate hypoxia (2500 to 4000m) modifies this response in both low and high altitude natives through metabolic compensation by elevating local aerobic capacity and possibly preventing muscle fiber atrophy. The combined use of classical morphometry and contemporary proteomic technology provides a highly resolved picture of the temporal control of hypoxia-induced muscular adaptations. The muscle proteome signature identifies mitochondrial autophagy and protein degradation as prime adaptive mechanisms to passive altitude exposure and ascent to extreme altitude. Protein measures also explain the lactate paradox by a sparing of glycolytic enzymes from general muscle wasting. Enhanced mitochondrial and angiogenic protein expression in human muscle with exercise up to 4000m is related to the reduction in intramuscular oxygen content below 1% (8torr), when the master regulator of hypoxia-dependent gene expression, HIF-1a, is stabilized. Accordingly, it is proposed here that the catabolic consequences of chronic hypoxia exposure reflect the insufficient activation of hypoxia-sensitive signaling and the suppression of energy-consuming protein translation.